Political Aspects of MNE Theory - Boddewyn, Jean J. (Journal of International Business Studies, 1988)
Political behavior by MNEs has usually been ignored, downplayed or passively treated in dominant economic models of the multinational enterprise. In order to remedy this lacuna. Dunning's eclectic paradigm is expanded to integrate political dimensions in the analysis of ownership, internalization and location advantages.